Nano-topography enhanced topological-cell-analysis in radiation-therapy - Pagliari, Francesca; Spadea, Maria-Francesca; Montay-Gruel, Pierre; Puspitasari-Kokko, Anggraeini; Seco, Joao; Tirinato, Luca; Accardo, Angelo; De Angelis, Francesco; Gentile, Francesco (Advanced healthcare materials, 2025)
Radiotherapy (RT) is a cancer treatment technique that involves exposing cells to ionizing radiation, including X-rays, electrons, or protons. RT offers promise to treat cancer, however, some inherent limitations can hamper its performance. Radio-resistance, whether innate or acquired, refers to the ability of tumor cells to withstand treatment, making it a key factor in RT failure. This perspective hypothesizes that nanoscale surface topography can impact on the topology of cancer cells network under radiation, and that this understanding can possibly advance the assessment of cell radio-resistance in RT applications. An experimental plan is proposed to test this hypothesis, using cancer cells exposed to various RT forms. By examining the influence of 2D surface and 3D scaffold nanoscale architecture on cancer cells, this approach diverges from traditional methodologies, such as clonogenic assays, offering a novel viewpoint that integrates fields such as tissue engineering, artificial intelligence, and nanotechnology. The hypotheses at the base of this perspective not only may advance cancer treatment but also offers insights into the broader field of structural biology. Nanotechnology and label-free Raman phenotyping of biological samples are lenses through which scientists can possibly better elucidate the structure-function relationship in biological systems.
Zuerst veröffentlicht: 22. März 2025
Gesehen am 06.10.2025